2016
DOI: 10.1186/s13006-017-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder views of breastfeeding education in schools: a systematic mixed studies review of the literature

Abstract: BackgroundBreastfeeding provides numerous health benefits for mothers and infants, but worldwide breastfeeding rates fall below recommendations. As part of efforts to increase breastfeeding initiation and duration, the World Health Organization and UNICEF UK recommend educational interventions to increase awareness and positive attitudes towards breastfeeding beginning during the school years. Breastfeeding education in the school setting offers the opportunity to improve the knowledge base, address misconcept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 39 publications
5
32
0
2
Order By: Relevance
“…Similar to findings in several countries around the world (Singletary et al, ), we are the first to show in Lebanon that intention among adolescents is significantly associated with attitude towards breastfeeding. In both males and females, intention was stronger when positive beliefs about the beneficial health outcomes of breastfeeding were stronger.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to findings in several countries around the world (Singletary et al, ), we are the first to show in Lebanon that intention among adolescents is significantly associated with attitude towards breastfeeding. In both males and females, intention was stronger when positive beliefs about the beneficial health outcomes of breastfeeding were stronger.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to attitudinal beliefs, and similar to other studies (Singletary et al, ), we found students' families to be influential on their intentions. Adolescents are more likely to support breastfeeding if they believed their families would approve.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations